Cardiotoxicity of Anticancer Therapeutics - Dong, Jerry; Chen, Hong (Frontiers in Cardiovascular Medicine, 2018)
As cancer therapeutics continues to improve and progress, the adverse side effects associated with anticancer treatments have also attracted more attention and have become extensively explored. Consequently, the importance of posttreatment follow-ups is becoming increasingly relevant to the discussion. Contemporary treatment methods, such as tyrosine kinase inhibitors, anthracycline chemotherapy, and immunotherapy regimens are effective in treating different modalities of cancers; however, these reagents act through interference with DNA replication or prevent DNA repair, causing endothelial dysfunction, generating reactive oxygen species, or eliciting non-specific immune responses. Therefore, cardiotoxic effects, such as hypertension, heart failure, and left ventricular dysfunction, arise posttreatment. Rising awareness of cardiovascular complications has led to meticulous attention for the evolution of treatment strategies and carefully monitoring between enhanced treatment effectiveness and minimization of adverse toxicity to the cardiovasculature, in which psychological assessments, early detection methods such as biomarkers, magnetic resonance imaging, and various drugs to reverse the damage from cardiotoxic events are more prevalent and their emphasis has increased tremendously. Fully understanding the mechanisms by which the risk factors action for various patients undergoing cancer treatment is also becoming more prevalent in preventing cardiotoxicity down the line.